2022
DOI: 10.1007/s12144-022-03207-7
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19, psychological distress, well-being and life satisfaction: A comparative study on first and second waves of COVID-19 among college students in India

Abstract: The aim of the study is to examine the relationship of fear of COVID-19 with well-being and life satisfaction through psychological distress among the college students in India. The study was conducted in two waves of the pandemic—during first and second waves of the COVID-19 among college students. A survey was conducted among 768 and 884 students in first and second waves of COVID-19 respectively for this purpose. Structural equation modeling was used to analyze the data. The study found out that the fear of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
(17 reference statements)
4
15
1
Order By: Relevance
“…The second hypothesis (H1b) is confirmed that economic hardship results in increasing individuals' depression levels in post-COVID-19 period in India as the P-value and β are equal to 0.0023 and 0.1678, respectively. To add more, the findings of our current study support the works of (Lathabhavan, 2022;Mekala et al, 2022). It means a positive relationship exists between individual depression levels and post-COVID-19 in the sec-ond wave.…”
Section: Discussionsupporting
confidence: 85%
“…The second hypothesis (H1b) is confirmed that economic hardship results in increasing individuals' depression levels in post-COVID-19 period in India as the P-value and β are equal to 0.0023 and 0.1678, respectively. To add more, the findings of our current study support the works of (Lathabhavan, 2022;Mekala et al, 2022). It means a positive relationship exists between individual depression levels and post-COVID-19 in the sec-ond wave.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, COVID-19 infection rates were starting to decrease across Europe [ 36 ]. In a longitudinal study with college students, Lathabhavan [ 72 ] also found a decrease in the indicators of positive adjustment as the number of deaths and infections worsened. It is also important to highlight that the socioeconomic challenges faced by many participants in South America cannot be neglected in the interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…References [ 56 , 60 ] found fear of CoV19 among students to have resulted in greater fear of colleagues within their social network, social isolation, and academic-related pain due to the radical change from conversional methods of learning to online learning. Finally, another apprehension of fear of Cov19 among students is the fear of missing out on significant and meaningful social experiences [ 61 , 62 ], which reduce life satisfaction [ 63 ].…”
Section: Literature Reviewmentioning
confidence: 99%